Gender-Specific Independent and Combined Effects of the Progesterone and 17-Hydroxyprogesterone on Metabolic Syndrome: From the Henan Rural Cohort Study - Wang M; Nie L; Wei D; Liu P; Zhang L; Fan K; Song Y; Wang L; Xu Q; Wang J; Liu X; Li L; et al. (Diabetes, Metabolic Syndrome and Obesity, 2021)
Mian Wang,1,* Luting Nie,1,* Dandan Wei,2 Pengling Liu,2 Li Zhang,2 Keliang Fan,2 Yu Song,1 Lulu Wang,2 Qingqing Xu,2 Juan Wang,2 Xiaotian Liu,2 Linlin Li,2 Zhenxing Mao,2 Chongjian Wang,2 Wenqian Huo1 1Department of Occupational and Environmental Health, College of Public Health, Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 2Department of Epidemiology and Biostatistics, College of Public Health, Zhengzhou University, Zhengzhou, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenqian HuoDepartment of Occupational and Environmental Health Sciences, College of Public Health, Zhengzhou University, 100 Kexue Avenue, Zhengzhou, 450001, Henan, People’s Republic of ChinaTel +86 371 67781452Fax +86 371 67781868Email huowenqian@zzu.edu.cnBackground: Although the concentrations of progesterone (P4) and 17-hydroxyprogesterone (17-OHP) have been correlated with some characteristics of metabolic syndrome (MetS), the relationships with MetS are inconclusive. Therefore, we investigated the relationship between P4 and 17-OHP with MetS.Methods: In all, the present study includes 4807 participants. Serum P4 and 17-OHP were measured through liquid chromatography-tandem mass spectrometry. Logistic regression and restricted cubic splines were used to assess the independent and combined effects of P4 and 17-OHP on MetS.Results: After adjusting for multiple variables, the positive association of P4 with MetS was observed in postmenopausal women (Third tertiles vs First tertiles: OR = 1.49, 95% CI: 1.20– 1.86) and the negative association of 17-OHP with MetS was observed in men (Third tertiles vs First tertiles: OR = 0.43, 95% CI: 0.32– 0.58). Compared with the combination of low P4 and low 17-OHP, the combination of high P4 and high 17-OHP were significantly related to MetS in postmenopausal women (OR = 1.71, 95% CI: 1.18– 2.48). Moreover, the combination of low P4 and high 17-OHP was negatively associated with MetS in men (OR = 0.41, 95% CI: 0.24– 0.69).Conclusion: The association between P4 and MetS in postmenopausal women was positive, whereas 17-OHP was negatively associated with MetS in men. Additionally, their combination has a synergistic effect on MetS in postmenopausal women and an antagonistic effect on MetS in men.Keywords: progesterone, 17-hydroxyprogesterone, metabolic syndrome, obesity